Aspek Maslahah dalam Praktik Poligami Perspektif Maqasid al-Syari’ah dan Regulasi Hukum Keluarga Islam di Indonesia - Hikmah, Nisrina Durratul; Muhasim, H. Ahmad (STAINI Press, 2025)
Polygamy is one of the important issues in Islamic family law that continues to be debated in various circles, both at the academic, social and political levels. In practice, many individuals are unable to fulfill the requirements of justice as stipulated in the Qur'an, so the practice of polygamy often results in negative impacts such as social inequality, gender injustice, and domestic conflict. This article aims to identify aspects of maṣlaḥah in the practice of polygamy from the perspective of maqaṣid al-syari'ah and legal regulations in Indonesia. Using a literature study approach, it is found that polygamy can provide maslahat in the context of protecting women, preserving offspring, social justice, and solving individual problems. However, the achievement of maslahat is highly dependent on the implementation of the principles of justice and responsibility. National regulations such as Law No. 1/1974 and KHI are important normative tools in ensuring the practice of polygamy in accordance with sharia values and the objectives of Islamic family law.